Diagnostic Performance of Precore Protein 22 Kilodalton Levels of HBV DNA in Chronic Hepatitis B Patients - Mas Aditya Senaputra; B. Rina A. Sidharta; Lusi Oka Wardhani (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2023)
Hepatitis B Virus (HBV) infection causes inflammation of the liver, which has a high prevalence in both Indonesia and the world. Serum HBV deoxyribonucleic acid (DNA) is important in determining the initiation therapy for Chronic Hepatitis B (CHB) patients. However, it has several limitations. Precore protein 22 kilodalton (p22cr) is synthesized from the HBV gene in hepatocytes, representing covalently closed circle (ccc) DNA. This study aimed to analyze the diagnostic performance of p22cr levels on HBV DNA in CHB patients. An observational analytic study with a cross-sectional approach was conducted on 83 CHB patients who were examined at the Clinical Pathology Laboratory of Dr. Moewardi General Academic Hospital in December 2020. Blood plasma samples were taken for HBV DNA and p22cr examination by using Polymerase Chain Reaction (PCR) and Enzyme-Linked Immunosorbent Assay (ELISA), respectively. The cut-off level of p22cr was determined by the Receiver Operating Curve (ROC) with the widest area Under the Curve (AUC). Sensitivity, specificity, Positive Predictive Value (PPV), Negative Predictive Value (NPV), Positive Likelihood Ratio (PLR), Negative Likelihood Ratio (NLR), and accuracy were calculated for the diagnostic performance of p22cr. The cut-off point of p22cr on HBV DNA > 20,000 IU/mL was 7.440 ng/mL with AUC 0.693 (p=0.003). The diagnostic performance of p22cr levels on HBV DNA obtained 44.44% sensitivity, 82.98% specificity, 66.67% PPV, 66.10% NPV, 2.61 PLR, 0.67 NLR, and 66.27% accuracy. P22cr level has a good specificity so it can be an alternative examination of HBV DNA in making decisions on therapy in patients with chronic hepatitis B. Further research needs to be done using HBcrAg and excluding elderly patients.